Magnesium-based hydrogen storage material as well as preparation method and application thereof

By developing an alloy based on Ni and Er ternary magnesium alloy system, the problems of high hydrogen absorption and discharge temperature and slow reaction rate in magnesium-based solid hydrogen storage technology are solved, and excellent hydrogen absorption and discharge performance at 350°C and below are achieved.

CN119614901APending Publication Date: 2025-03-14CHONGQING UNIV +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411809493.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Magnesium-based solid hydrogen storage technology has the problems of high hydrogen absorption and discharge temperature and slow reaction rate, which limits its wide application.

Method used

An alloy based on a ternary magnesium alloy system composed of Ni and Er is developed, and a magnesium-based hydrogen storage material is prepared by vacuum smelting and ball milling, and its microstructure is optimized to improve hydrogen absorption and discharge performance.

Benefits of technology

It has achieved excellent hydrogen absorption and release performance at 350°C and below, fast hydrogen release speed, high hydrogen absorption amount, and better performance than other rare earth metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614901A_ABST
    Figure CN119614901A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogen storage materials, and particularly relates to a magnesium-based hydrogen storage material and a preparation method and application thereof. The magnesium-based hydrogen storage material comprises the following components in percentage by mass: 2-12% of Er, 2-12% of Ni, inevitable impurities and the balance of Mg. The hydrogen storage material has excellent hydrogen absorption and desorption capacity, and the hydrogen desorption capacity can reach 6.16 wt.% at the temperature of 350 DEG C and the pressure of 4 MPa for 5 min; the hydrogen absorption capacity can reach 5.77 wt.% in 10 minutes at the temperature of 300 DEG C and the pressure of 4 MPa; the hydrogen absorption capacity can reach 5.7 wt.% at the temperature of 250 DEG C and under the pressure of 4 MPa for 20 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen storage materials, and in particular relates to a magnesium-based hydrogen storage material and a preparation method and application thereof. Background Art

[0002] Hydrogen energy has the characteristics of abundant resources, carbon-free, high energy density (120MJ / kg), and diverse application scenarios. It has great potential in reducing environmental pollution and promoting energy transformation. At present, safe and efficient hydrogen storage and transportation technology is one of the main bottlenecks restricting the development of the hydrogen energy industry chain.

[0003] Compared with traditional hydrogen storage technology, solid-state hydrogen storage technology based on magnesium-based materials has the advantages of low cost, high hydrogen storage density (7.6wt.% and 110gH2 / L), safety, high efficiency and good reversibility, which opens up greater possibilities for the large-scale utilization of hydrogen energy. However, the inherent thermodynamic and kinetic challenges of magnesium-based hydrogen storage still exist, which directly leads to the disadvantages of high hydrogen absorption and desorption temperature (>350℃) and slow reaction rate. Therefore, solving these problems remains the main scientific challenge for the widespread application of magnesium-based solid-state hydrogen storage technology.

[0004] Alloying is one of the simple and efficient ways to improve the hydrogen storage performance of MgH2, which is conducive to achieving the goal of industrialization. Existing studies have found that alloys based on transition metals and rare earth metals that form a ternary magnesium alloy system can form a long-period phase very well. After the first activation, the long-period phase decomposes into nanocrystals, which can provide more active sites for the reaction, and provide more active sites and diffusion channels for the dissociation and transfer of hydrogen. It can still have good hydrogen charging and decomposition performance at 350°C and below, and can achieve better hydrogen storage. Therefore, it is of great potential to develop an alloy based on a ternary magnesium alloy system composed of transition metals and rare earth metals as a hydrogen storage material. Summary of the invention

[0005] The present invention develops an alloy based on a ternary magnesium alloy system composed of Ni (transition metal) and Er (rare earth metal) as a hydrogen storage material, which has excellent hydrogen absorption and desorption properties at 350°C and below, and its performance is better than that of ternary magnesium alloys composed of other rare earth metals, such as Gd.

[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:

[0007] In one aspect, the present invention provides a magnesium-based hydrogen storage material, which comprises, by mass percentage, 2%-12% of Er, 2%-12% of Ni, unavoidable impurities and the remainder of Mg.

[0008] Preferably, in the above magnesium-based hydrogen storage material, the mass percentage of Mg is ≥ 90%, and the mass fraction of Ni is ≥ the mass fraction of Er.

[0009] Preferably, in the above magnesium-based hydrogen storage material, the mass percentage of Mg is ≥90%, and the mass fraction of Ni is ≥the mass fraction of Er, and the mass fraction of Ni is 5%-7.8%.

[0010] Preferably, the above-mentioned magnesium-based hydrogen storage material is selected from any one of the following materials: (a) the magnesium-based hydrogen storage material comprises, by mass percentage, 7.8% Ni, 2.2% Er, inevitable impurities and the remainder Mg; (b) the magnesium-based hydrogen storage material comprises, by mass percentage, 2.2% Ni, 7.8% Er, inevitable impurities and the remainder Mg; (c) the magnesium-based hydrogen storage material comprises, by mass percentage, 6.5% Ni, 3.5% Er, inevitable impurities and the remainder Mg; (d) the magnesium-based hydrogen storage material comprises, by mass percentage, 5% Ni, 5% Er, inevitable impurities and the remainder Mg; (e) the magnesium-based hydrogen storage material comprises, by mass percentage, 5% Ni, 5% Er, inevitable impurities and the remainder Mg; The hydrogen storage material comprises, by mass percentage, 2% Ni, 12% Er, inevitable impurities and the balance Mg; (f) the magnesium-based hydrogen storage material comprises, by mass percentage, 12% Ni, 2% Er, inevitable impurities and the balance Mg; (g) the magnesium-based hydrogen storage material comprises, by mass percentage, 7% Ni, 5% Er, inevitable impurities and the balance Mg; (h) the magnesium-based hydrogen storage material comprises, by mass percentage, 6% Ni, 6% Er, inevitable impurities and the balance Mg; (i) the magnesium-based hydrogen storage material comprises, by mass percentage, 5% Ni, 3% Er, inevitable impurities and the balance Mg.

[0011] In another aspect, the present invention provides a method for preparing the magnesium-based hydrogen storage material of the present invention, comprising: (1) mixing a magnesium ingot, a Mg-Ni master alloy and a Mg-Er master alloy, smelting the mixture, and casting to obtain a Mg-Ni-Er alloy; and (2) preparing the Mg-Ni-Er alloy into a Mg-Ni-Er alloy powder to obtain a magnesium-based hydrogen storage material.

[0012] Preferably, the preparation method satisfies one or more combinations of the following conditions: (a) in step (1), the purity of the magnesium ingot is ≥99%; (b) in step (1), smelting comprises: smelting in a vacuum smelting furnace in a first stage and a second stage, the power of the first stage is ≥15kW, and the power of the second stage is ≥35KW; the smelting time of the first stage and the second stage is ≥5min respectively; (c) in step (2), preparing the Mg-Ni-Er alloy into Mg-Ni-Er alloy powder comprises: crushing the Mg-Ni-Er alloy and ball milling to obtain the Mg-Ni-Er alloy powder; (d) the diameter of the Mg-Ni-Er alloy powder is ≤15um.

[0013] Preferably, the ball milling satisfies one or more combinations of the following conditions: 1) the ball milling is performed under an inert gas environment; 2) the ball milling is performed by mechanical wet ball milling.

[0014] Preferably, the mechanical wet ball milling satisfies one or more combinations of the following conditions: (i) the ball milling solvent is selected from one or more combinations of n-heptane, ethanol, isopropanol or ethyl acetate; (ii) the ball-to-material ratio is (20-40):1; (iii) the ball milling speed is 250rpm-350rpm; (iv) the diameter of the grinding balls is 8mm and 6mm.

[0015] Another aspect of the present invention provides a hydrogen storage device, which is prepared from the magnesium-based hydrogen storage material of the present invention.

[0016] Another aspect of the present invention provides an application of the magnesium-based hydrogen storage material of the present invention in solid-state hydrogen storage.

[0017] The beneficial effects of the present invention include at least:

[0018] (1) The magnesium-based hydrogen storage material provided by the present invention has excellent hydrogen absorption and desorption capabilities. At 350°C (4MPa), the hydrogen desorption can reach 6.16wt.% in 5 minutes; at 300°C (4MPa), the hydrogen absorption can reach 5.77wt.% in 10 minutes; and at 250°C (4MPa), the hydrogen absorption can reach 5.7wt.% in 20 minutes.

[0019] (2) The magnesium-based hydrogen storage material provided by the present invention has an excellent hydrogen release rate. It only takes 2 minutes to release 6.3 wt.% of hydrogen after hydrogenation at 300°C (4 MPa); and at 350°C (4 MPa), the hydrogen absorption amount can reach 6.44 wt.% within 60 minutes.

[0020] (3) Compared with the magnesium-based hydrogen storage material based on Gd composition, the magnesium-based hydrogen storage material provided by the present invention can improve the hydrogen release amount at 350°C (4MPa) for 5 minutes by about 6%; the hydrogen absorption amount at 300°C (4MPa) for 10 minutes by about 20%; the hydrogen absorption amount at 250°C (4MPa) for 20 minutes by about 24%.

[0021] (4) In the magnesium-based hydrogen storage material provided by the present invention, when the mass fraction of Mg ≥ 90% and the mass fraction of Ni ≥ the mass fraction of Er, the hydrogen absorption and desorption performance of the hydrogen storage material is much better than that of the hydrogen storage material with Mg < 90% and the mass fraction of Ni ≥ the mass fraction of Er; for example, the performance of Mg-5wt.%Ni-5wt.%Er alloy is much better than that of Mg-6wt.%Ni-6wt.%Er alloy; for another example, the performance of Mg-7.8wt.%Ni-2.2wt.%Er alloy is much better than that of Mg-12wt.%Ni-2wt.%Er alloy.

[0022] (5) The preparation method of the magnesium-based hydrogen storage material provided by the present invention can be obtained by vacuum melting and ball milling. The preparation method is simple and meets the industrial application requirements of the magnesium-based hydrogen storage material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the Mg-Ni-Er alloy prepared in Example 1;

[0024] Figure 2 This is a SEM image of the ball-milled Mg-Ni-Er alloy prepared in Example 1;

[0025] Figure 3 is the XRD pattern of the Mg-Ni-Er alloy prepared in Example 1;

[0026] Figure 4 The isothermal hydrogen release curves of the magnesium-based hydrogen storage material prepared in Example 1 at different temperatures;

[0027] Figure 5 The isothermal hydrogen absorption curves of the magnesium-based hydrogen storage material prepared in Example 1 at different temperatures;

[0028] Figure 6 This is the hydrogen absorption and desorption curve of the magnesium-based hydrogen storage material prepared in Example 1 at 300°C for 40 cycles. DETAILED DESCRIPTION

[0029] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.

[0030] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, materials, or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, materials, or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.

[0031] The embodiment of the present invention provides a magnesium-based hydrogen storage material, which comprises, by mass percentage, 2%-12% of Er, 2%-12% of Ni, unavoidable impurities and the remainder of Mg.

[0032] It should be noted that the magnesium-based hydrogen storage material in the present invention is a Mg-Ni-Er alloy. On the one hand, the Mg2Ni phase formed can promote the dissociation of H2 and play a good role as a "hydrogen pump". After ball milling, the Mg2Ni phase becomes finer, which provides a large number of active sites for the dissociation and diffusion of hydrogen, and promotes the stable and efficient hydrogen storage dynamics of MgH2; on the other hand, Er is dissolved in the Mg matrix, causing lattice distortion, effectively promoting Mg-H dissociation, greatly improving the thermodynamic stability of MgH2, and has good application prospects in solid-state hydrogen storage.

[0033] It should also be noted that the magnesium-based hydrogen storage material in the present invention includes, by mass percentage, Er 2%-12%, Ni 2%-12%, unavoidable impurities and the remainder Mg; wherein Er may be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 11%, etc., and Er may be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 11%, etc.; in addition, unavoidable impurities refer to a small amount of non-metallic elements, metal elements or compounds that cannot be completely removed and remain in the metal during metal smelting and processing due to limitations of raw materials, process conditions and other factors.

[0034] In some specific examples, in the magnesium-based hydrogen storage material, the mass percentage of Mg is ≥ 90%, and the mass fraction of Ni is ≥ the mass fraction of Er.

[0035] It should be noted that the magnesium-based hydrogen storage material in the present invention preferably has a Mg mass percentage ≥ 90%, and a Ni mass fraction ≥ the Er mass fraction; for example, the Mg mass percentage may be 91%, 92%, 93%, 94% or 95%, etc., and the mass fractions of Ni and Er may be adaptively regulated according to the Mg mass percentage; when the Mg mass percentage is < 90% and the Ni mass fraction is ≥ the Er mass fraction, the hydrogen absorption and desorption performances of the magnesium-based hydrogen storage material are not as good as those of the Mg mass percentage ≥ 90% and the Ni mass fraction is ≥ the Er mass fraction; for example, the performance of the Mg-5wt.%Ni-5wt.%Er alloy is much better than that of the Mg-6wt.%Ni-6wt.%Er alloy; for another example, the performance of the Mg-7.8wt.%Ni-2.2wt.%Er alloy is much better than that of the Mg-12wt.%Ni-2wt.%Er alloy.

[0036] In some specific examples, in the magnesium-based hydrogen storage material, the mass percentage of Mg is ≥90%, and the mass fraction of Ni is ≥the mass fraction of Er, and the mass fraction of Ni is 5%-7.8%.

[0037] It should be noted that, in the magnesium-based hydrogen storage material of the present invention, based on the mass percentage of Mg being ≥90% and the mass fraction of Ni being ≥the mass fraction of Er, the mass fraction of Ni is preferably 5%-7.8%, such as 5.3%, 5.5%, 5.8%, 6%, 6.2%, 6.4%, 6.8%, 7%, 7.3%, 7.5% or 7.7%, etc.

[0038] In some specific examples, the magnesium-based hydrogen storage material is selected from any one of the following materials:

[0039] (a) The magnesium-based hydrogen storage material includes 7.8% Ni, 2.2% Er, unavoidable impurities and the remainder Mg according to mass percentage; the magnesium-based hydrogen storage material with this ratio can release hydrogen at 350°C (4MPa) for 5 minutes and 5.16wt.% at 300°C (4MPa) for 10 minutes; and can absorb hydrogen at 5.7wt.% at 250°C (4MPa) for 20 minutes.

[0040] (b) The magnesium-based hydrogen storage material includes 2.2% Ni, 7.8% Er, unavoidable impurities and the remainder Mg according to mass percentage; the magnesium-based hydrogen storage material with this ratio can release hydrogen at 350°C (4MPa) for 5 minutes and 5.19wt.% at 300°C (4MPa) for 10 minutes; and can absorb hydrogen at 3.7wt.% at 250°C (4MPa) for 20 minutes.

[0041] (c) The magnesium-based hydrogen storage material comprises 6.5% Ni, 3.5% Er, unavoidable impurities and the remainder Mg in terms of mass percentage; the magnesium-based hydrogen storage material with this ratio can release 5.86wt.% of hydrogen in 5 minutes at 350°C (4MPa); absorb 5.6wt.% of hydrogen in 10 minutes at 300°C (4MPa); and absorb 5.3wt.% of hydrogen in 20 minutes at 250°C (4MPa);

[0042] (d) The magnesium-based hydrogen storage material includes 5% Ni, 5% Er, unavoidable impurities and the remainder Mg according to mass percentage; the magnesium-based hydrogen storage material with this ratio can release hydrogen at 5.8wt.% in 5 minutes at 350°C (4MPa); absorb hydrogen at 5.54wt.% in 10 minutes at 300°C (4MPa); and absorb hydrogen at 5.0wt.% in 20 minutes at 250°C (4MPa);

[0043] (e) The magnesium-based hydrogen storage material comprises Ni2%, Er12%, unavoidable impurities and the remainder Mg in terms of mass percentage; the magnesium-based hydrogen storage material with this ratio can release 5.7wt.% of hydrogen in 5 minutes at 350°C (4MPa); absorb 4.3wt.% of hydrogen in 10 minutes at 300°C (4MPa); and absorb 3.9wt.% of hydrogen in 20 minutes at 250°C (4MPa);

[0044] (f) The magnesium-based hydrogen storage material includes 12% Ni, 2% Er, unavoidable impurities and the remainder Mg in terms of mass percentage; the magnesium-based hydrogen storage material with this ratio can release 5.5wt.% of hydrogen in 5 minutes at 350°C (4MPa); absorb 5.2wt.% of hydrogen in 10 minutes at 300°C (4MPa); and absorb 4.9wt.% of hydrogen in 20 minutes at 250°C (4MPa);

[0045] (g) The magnesium-based hydrogen storage material comprises 7% Ni, 5% Er, unavoidable impurities and the remainder Mg according to mass percentage; the magnesium-based hydrogen storage material with this ratio can release 5.6wt.% of hydrogen in 5 minutes at 350°C (4MPa); can absorb 5.3wt.% of hydrogen in 10 minutes at 300°C (4MPa); and can absorb 4.8wt.% of hydrogen in 20 minutes at 250°C (4MPa);

[0046] (h) The magnesium-based hydrogen storage material comprises 6% Ni, 6% Er, unavoidable impurities and the remainder Mg in terms of mass percentage; the magnesium-based hydrogen storage material with this ratio can release 5.4wt.% hydrogen in 5 minutes at 350°C (4MPa); absorb 5.1wt.% hydrogen in 10 minutes at 300°C (4MPa); and absorb 4.6wt.% hydrogen in 20 minutes at 250°C (4MPa).

[0047] (i) The magnesium-based hydrogen storage material comprises 5% Ni, 3% Er, unavoidable impurities and the remainder Mg in terms of mass percentage; the magnesium-based hydrogen storage material with this ratio can release 5.5wt.% hydrogen in 5 minutes at 350°C (4MPa); absorb 5.2wt.% hydrogen in 10 minutes at 300°C (4MPa); and absorb 4.9wt.% hydrogen in 20 minutes at 250°C (4MPa).

[0048] The embodiment of the present invention also provides a method for preparing the magnesium-based hydrogen storage material of the present invention, comprising: (1) mixing a magnesium ingot, a Mg-Ni master alloy and a Mg-Er master alloy, smelting the mixture, and casting to obtain a Mg-Ni-Er alloy; and (2) preparing the Mg-Ni-Er alloy into a Mg-Ni-Er alloy powder to obtain a magnesium-based hydrogen storage material.

[0049] It should be noted that the operations such as “melting” and “casting” in the present invention are conventional operations in the art and have no specific meanings. The specific operation methods of the above operations can be selected according to the specific preparation environment.

[0050] In some specific examples, the above preparation method satisfies one or more combinations of the following conditions:

[0051] (a) In step (1), the purity of the magnesium ingot is ≥99%;

[0052] (b) In step (1), the smelting comprises: smelting in a vacuum smelting furnace in a first stage and a second stage, the power of the first stage is ≥15 kW, and the power of the second stage is ≥35 kW; the smelting time of the first stage and the second stage are both ≥5 min;

[0053] (c) In step (2), preparing the Mg-Ni-Er alloy into Mg-Ni-Er alloy powder comprises: crushing the Mg-Ni-Er alloy, and ball milling to obtain the Mg-Ni-Er alloy powder;

[0054] (d); The diameter of the Mg-Ni-Er alloy powder is ≤15um; specifically, the diameter of the Mg-Ni-Er alloy powder can be ≤13um, ≤12um or ≤10um, etc., and different particle sizes can be obtained according to different processes; the general particle size can be 5um-15um.

[0055] It should be noted that the operations such as "crushing" and "ball milling" in the present invention are conventional operations in the field and have no specific meanings. The specific operation methods of the above operations can be selected according to the specific preparation environment; for example, the "crushing" in the present invention can be performed in the form of grinding.

[0056] It should also be noted that the above preparation method satisfies any one of the above conditions (a) to (c), and preferably satisfies all of the above conditions at the same time.

[0057] In some specific examples, the ball milling satisfies one or more combinations of the following conditions:

[0058] 1) ball milling is performed in an inert gas environment; specifically, the inert gas is a gas environment known in the art, such as argon, nitrogen or helium; in addition, the purpose of ball milling in an inert gas environment is to reduce oxidation of the sample and corrosion of the ball milling equipment;

[0059] 2) Ball milling: Mechanical wet ball milling is selected; specifically, any ball milling method known in the art can be selected in the present invention, and mechanical wet ball milling is preferred, as the ball milling effect is better than other ball milling methods.

[0060] It should also be noted that the ball milling can satisfy any one of the above conditions 1) to 2), and preferably all of the above conditions are satisfied at the same time.

[0061] In some specific examples, the mechanical wet ball milling satisfies one or more combinations of the following conditions:

[0062] (i) the ball milling solvent is selected from one or more combinations of n-heptane, ethanol, isopropanol or ethyl acetate; specifically, the ball milling solvent is preferably n-heptane, which has better effects than other solvents;

[0063] (ii) The ball-to-material ratio is (20-40):1; specifically, the ball-to-material ratio is the mass ratio of the grinding balls to the Mg-Ni-Er alloy, which can be 24:1, 27:1, 30:1, 33:1, 35:1 or 38:1, etc.;

[0064] (iii) the ball milling speed is 250 rpm-350 rpm, such as 280 rpm, 300 rpm or 320 rpm;

[0065] (iv) The diameters of the grinding balls are 8 mm and 6 mm; specifically, the diameters of the grinding balls can be arbitrarily selected, and mixed grinding balls with diameters of 8 mm and 6 mm are preferred.

[0066] It should be noted that the mechanical wet ball milling can satisfy any one of the above conditions (i) to (iv), and preferably satisfies all of the above conditions at the same time.

[0067] An embodiment of the present invention further provides a hydrogen storage device, which is prepared from the magnesium-based hydrogen storage material of the present invention.

[0068] It should be noted that the magnesium-based hydrogen storage material in the present invention has excellent hydrogen absorption and release properties, and can be prepared into different hydrogen storage devices, such as for use in fuel cells, hydride hydrogen storage devices, heat storage and heat transfer devices, and hydrogen separation and recovery devices.

[0069] An embodiment of the present invention further provides an application of the magnesium-based hydrogen storage material of the present invention in solid-state hydrogen storage.

[0070] It should be noted that, as mentioned above, the magnesium-based hydrogen storage material in the present invention has excellent hydrogen absorption and release properties and has excellent solid-state hydrogen storage potential.

[0071] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.

[0072] 1. Preparation and characterization of magnesium-based hydrogen storage materials

[0073] In the following embodiments, "Mg-30wt.%Ni" refers to a Ni-Mg alloy containing 30wt% Ni and the rest Mg, and other such expressions have the same meanings; Mg-7.8wt.%Ni-2.2wt.%Er refers to a Ni-Er-Mg alloy containing 7.8wt% Ni and 2.2wt% Er at the same time and the rest Mg, and other such expressions have the same meanings.

[0074] Example 1

[0075] (1) Preparation of Mg-Ni-Er alloy: 3400 g of pure Mg, 1326 g of Mg-30 wt.% Ni and 374 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 20 kW for 10 minutes, and then melted at a power of 40 kW for 10 minutes and cast to obtain a Mg-Ni-Er alloy;

[0076] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared as above was crushed into powder, and 5 g of the powder was subjected to mechanical wet ball milling in an argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 280 rpm, ball milling jar of 250 mL, stainless steel grinding balls with diameters of 8 mm and 6 mm, 2 grinding balls with a diameter of 8 mm, and the rest with 6 mm grinding balls) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 7.8 wt.% Ni, 2.2 wt.% Er and unavoidable impurities and remainder Mg (also marked as Mg-7.8 wt.% Ni-2.2 wt.% Er, the same below).

[0077] The SEM image of the Mg-Ni-Er alloy prepared in step (1) is as follows: Figure 1 As shown, it can be seen that there are more Mg2Ni phases gathered at the grain boundaries of the Mg-Ni-Er alloy obtained after smelting.

[0078] The SEM image of the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy prepared in step (2) is as follows: Figure 2 As shown, it can be seen that the particle size of the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy is about 5um-15um.

[0079] The XRD pattern of the Mg-Ni-Er alloy prepared in step (1) is as follows: Figure 3 As shown, it can be seen that the Mg-Ni-Er alloy is mainly composed of α-Mg phase and Mg2Ni phase.

[0080] Example 2

[0081] The difference between Example 2 and Example 1 is that the amount of raw materials added is different; the amount of raw materials added in Example 2 is: 3400g of pure Mg, 374g of Mg-30wt.% Ni, 1326g of Mg-30wt.% Er; the other steps are the same as Example 1; the prepared magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 2.2wt.% Ni, 7.8wt.% Er, and unavoidable impurities and residual Mg.

[0082] Example 3

[0083] (1) Preparation of Mg-Ni-Er alloy: 3400 g of pure Mg, 850 g of Mg-30 wt.% Ni and 850 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0084] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared as above was crushed into powder, and 5 g of the powder was subjected to mechanical wet ball milling in an argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, stainless steel grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 5 wt.% Ni, 5 wt.% Er, and unavoidable impurities and the remainder of Mg.

[0085] Example 4

[0086] (1) Preparation of Mg-Ni-Er alloy: 3400 g of pure Mg, 1105 g of Mg-30 wt.% Ni and 595 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0087] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 5 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 6.5 wt.% Ni, 3.5 wt.% Er and unavoidable impurities and the remainder of Mg.

[0088] Example 5

[0089] (1) Preparation of Mg-Ni-Er alloy: 2720 g of pure Mg, 340 g of Mg-30 wt.% Ni and 2040 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0090] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 5 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 2 wt.% Ni, 12 wt.% Er and unavoidable impurities and the remainder of Mg.

[0091] Example 6

[0092] (1) Preparation of Mg-Ni-Er alloy: 2720 g of pure Mg, 2040 g of Mg-30 wt.% Ni and 340 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0093] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 5 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 12 wt.% Ni, 2 wt.% Er and unavoidable impurities and the remainder of Mg.

[0094] Example 7

[0095] (1) Preparation of Mg-Ni-Er alloy: 3060 g of pure Mg, 1190 g of Mg-30 wt.% Ni and 850 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0096] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 5 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 7 wt.% Ni, 5 wt.% Er and unavoidable impurities and the remainder of Mg.

[0097] Example 8

[0098] (1) Preparation of Mg-Ni-Er alloy: 2720 g of pure Mg, 1020 g of Mg-30 wt.% Ni and 1020 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0099] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 5 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 6 wt.% Ni, 6 wt.% Er and unavoidable impurities and the remainder of Mg.

[0100] Example 9

[0101] (1) Preparation of Mg-Ni-Er alloy: 3740 g of pure Mg, 850 g of Mg-30 wt.% Ni and 510 g of Mg-30 wt.% Er were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 15 kW for 5 min, and then melted at a power of 35 kW for 5 min and cast to obtain a Mg-Ni-Er alloy;

[0102] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Er alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 5 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 30:1, ball milling speed of 250 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Er alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy includes 5 wt.% Ni, 3 wt.% Er and unavoidable impurities and the remainder of Mg.

[0103] Comparative Example 1

[0104] The difference between Comparative Example 1 and Example 1 is that the amount of raw materials added is different; the amount of raw materials added in Comparative Example 1 is: 3400g of pure Mg, 1700g of Mg-30wt.% Ni; the other steps are the same as Example 1; the prepared magnesium-based hydrogen storage material based on Mg-Ni alloy includes 10wt.% Ni and unavoidable impurities and residual Mg.

[0105] Comparative Example 2

[0106] The difference between Comparative Example 2 and Example 1 is that the amount of raw materials added is different; the amount of raw materials added in Comparative Example 2 is: 3400g of pure Mg, 1700g of Mg-30wt.% Er; the other steps are the same as Example 1; the prepared magnesium-based hydrogen storage material based on Mg-Er alloy includes 10wt.% Er and unavoidable impurities and residual Mg.

[0107] Comparative Example 3

[0108] (1) Preparation of Mg-Ni-Gd alloy: 3400 g of pure Mg, 1326 g of Mg-30 wt.% Ni and 374 g of Mg-30 wt.% Gd were weighed respectively, placed in a vacuum melting furnace, and stirred while melting at a power of 20 kW for 10 minutes, and then melted at a power of 40 kW for 10 minutes and cast to obtain a Mg-Ni-Gd alloy;

[0109] (2) Preparation of magnesium-based hydrogen storage material based on Mg-Ni-Gd alloy: The Mg-Ni-Er alloy prepared above was crushed into powder, and 15 g was taken for mechanical wet ball milling under argon atmosphere (n-heptane as solvent, ball-to-material ratio of 20:1, ball milling speed of 280 rpm, ball milling jar of 500 mL stainless steel jar, grinding balls with diameters of 8 mm and 6 mm, and the number of grinding balls was the same as in Example 1) for 10 h to obtain magnesium-based hydrogen storage material based on Mg-Ni-Gd alloy; the magnesium-based hydrogen storage material based on Mg-Ni-Gd alloy includes 7.8 wt.% Ni, 2.2 wt.% Gd, and unavoidable impurities and the remainder of Mg.

[0110] 2. Hydrogen absorption and desorption test of magnesium-based hydrogen storage materials

[0111] In a glove box, 150 mg of the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy prepared in Example 1 (Mg-7.8wt.% Ni-2.2wt.% Er alloy powder) was weighed, and the temperature-dependent hydrogen desorption curve of the sample was tested using a PCTpro high-pressure gas adsorption instrument: isothermal hydrogen desorption curves under an initial hydrogen pressure of 0.01 MPa at 225°C, 250°C, 275°C, 300°C, 325°C and 350°C; isothermal hydrogen absorption curves under an initial hydrogen pressure of 4 MPa at 225°C, 250°C, 275°C, 300°C, 325°C and 350°C; and 50 cycles of hydrogen absorption and desorption curves at 300°C.

[0112] The isothermal hydrogen desorption curves of the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy prepared in Example 1 at different temperatures and an initial hydrogen pressure of 0.01 MPa are as follows: Figure 4 As shown, the results show that it can release 5.9wt.% hydrogen in 22min at 260℃; at 300℃, it only takes 2min to release 6.3wt.% hydrogen; the above shows that the magnesium-based hydrogen storage material prepared in Example 1 not only has a lower initial hydrogen desorption temperature, but also the hydrogen desorption kinetics is significantly improved.

[0113] The isothermal hydrogen absorption curves of the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy prepared in Example 1 at different temperatures under an initial hydrogen pressure of 4 MPa are as follows: Figure 5 As shown, the results show that it can absorb 6.44wt.% of hydrogen within 60min at 350°C, which means that the hydrogen absorption kinetics of the magnesium-based hydrogen storage material prepared in Example 1 is significantly improved.

[0114] The 40-cycle hydrogen absorption and desorption curve of the magnesium-based hydrogen storage material based on Mg-Ni-Er alloy prepared in Example 1 at 300°C and an initial hydrogen pressure of 3MPa is as follows: Figure 6As shown, the results show that after 40 cycles of hydrogen absorption and desorption, the cycle capacity of the ball-milled Mg-7.8wt.%Ni-2.2wt.%Er alloy powder still remains above 5.7wt.%, showing stable cycle reversibility.

[0115] In addition, a calibrated PCTpro high-pressure gas adsorption instrument (Setaram Instruments, France) was used to test the hydrogen release amount of the magnesium-based hydrogen storage materials based on Mg-Ni-Er alloy in Examples 1 to 9 and Comparative Examples 1 to 3 at 350°C and an initial hydrogen pressure of 4 MPa for 5 minutes, the hydrogen absorption amount at 300°C and an initial hydrogen pressure of 4 MPa for 10 minutes, and the hydrogen absorption amount at 250°C and an initial hydrogen pressure of 4 MPa for 20 minutes. The results are shown in Table 1 below.

[0116] Table 1 Hydrogen absorption and desorption of different magnesium-based hydrogen storage materials based on Mg-Ni-Er alloys

[0117]

[0118]

[0119] It can be seen from Table 1 above that the magnesium-based hydrogen storage material containing both Ni and Er has excellent hydrogen absorption and desorption performance. At 350°C (4MPa), the hydrogen desorption amount can reach 6.16wt.% in 5min; at 300°C (4MPa), the hydrogen absorption amount can reach 5.77wt.% in 10min; at 250°C (4MPa), the hydrogen absorption amount can reach 5.7wt.% in 20min (Example 1); and all (Examples 1 to 9) are far superior to the hydrogen absorption and desorption performance of the magnesium-based hydrogen storage material containing only Ni or Er; and the hydrogen absorption and desorption performance of the magnesium-based hydrogen storage material containing both Ni and Er is also far superior to the hydrogen absorption and desorption performance of the magnesium-based hydrogen storage material containing both Ni and Gd. The hydrogen absorption and desorption performances are far superior to those of magnesium-based hydrogen storage materials containing only Ni or Er; for example, for the hydrogen desorption at 350°C (4MPa) in 5 min, the magnesium-based hydrogen storage material containing both Ni and Er is increased by about 6% compared with the magnesium-based hydrogen storage material containing both Ni and Gd; for the hydrogen absorption at 300°C (4MPa) in 10 min, the magnesium-based hydrogen storage material containing both Ni and Er is increased by about 20% compared with the magnesium-based hydrogen storage material containing both Ni and Gd; for the hydrogen absorption at 250°C (4MPa) in 20 min, the magnesium-based hydrogen storage material containing both Ni and Er is increased by about 24% compared with the magnesium-based hydrogen storage material containing both Ni and Gd.

[0120] In addition, by comparing Example 1, Example 3, Example 4 and Example 2, it can be learned that when the mass fraction of Mg is the same as 90%, the hydrogen absorption and desorption performances of the hydrogen storage material with a mass fraction of Ni ≥ the mass fraction of Er are better than those of the hydrogen storage material with a mass fraction of Ni < the mass fraction of Er. For example, the hydrogen absorption and desorption performances of the hydrogen storage material of Example 1 are better than those of the hydrogen storage material of Example 2.

[0121] In addition, by comparing Example 1 and Example 9 with Example 6 and Example 7 or comparing Example 3 and Example 8, it can be learned that when the mass fraction of Ni is ≥ the mass fraction of Er, the hydrogen absorption and desorption performance of the hydrogen storage material with a mass fraction of Mg ≥ 90% is better than that of the hydrogen storage material with a mass fraction of Mg < 90%. For example, the hydrogen absorption and desorption performance of the hydrogen storage materials of Example 1 and Example 9 is better than that of Example 6 and Example 7, and for example, the hydrogen absorption and desorption performance of the hydrogen storage material of Example 3 is better than that of Example 9.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.

Claims

1. A magnesium-based hydrogen storage material, characterized in that: Calculated by mass percentage, it includes Er 2%-12%, Ni 2%-12%, inevitable impurities and the balance Mg.

2. The magnesium-based hydrogen storage material according to claim 1, characterized in that: The mass percentage of Mg is ≥ 90%, and the mass fraction of Ni is ≥ the mass fraction of Er.

3. The magnesium-based hydrogen storage material according to claim 2, characterized in that: The mass fraction of Ni is 5%-7.8%.

4. The magnesium-based hydrogen storage material according to claim 1, characterized in that The magnesium-based hydrogen storage material can be selected from any of the following materials: (a) The magnesium-based hydrogen storage material comprises, by mass percentage, 7.8% Ni, 2.2% Er, unavoidable impurities and the balance Mg; (b) a magnesium-based hydrogen storage material comprising, by mass percentage, 2.2% Ni, 7.8% Er, unavoidable impurities and the balance Mg; (c) a magnesium-based hydrogen storage material comprising, by mass percentage, 6.5% Ni, 3.5% Er, unavoidable impurities and the balance Mg; (d) a magnesium-based hydrogen storage material, comprising 5% Ni, 5% Er, unavoidable impurities and the balance Mg, in terms of mass percentage; (e) a magnesium-based hydrogen storage material comprising, by mass percentage, 2% Ni, 12% Er, unavoidable impurities and the balance Mg; (f) a magnesium-based hydrogen storage material comprising, by mass percentage, 12% Ni, 2% Er, unavoidable impurities and the balance Mg; (g) a magnesium-based hydrogen storage material comprising, by mass percentage, 7% Ni, 5% Er, unavoidable impurities and the balance Mg; (h) The magnesium-based hydrogen storage material comprises, by mass percentage, 6% Ni, 6% Er, inevitable impurities and the balance Mg; (i) The magnesium-based hydrogen storage material comprises, by mass percentage, 5% Ni, 3% Er, inevitable impurities and the balance Mg.

5. The method for preparing the magnesium-based hydrogen storage material according to any one of claims 1 to 4, characterized in that: include: (1) mixing a magnesium ingot, a Mg-Ni master alloy and a Mg-Er master alloy, smelting the mixture, and casting the mixture to obtain a Mg-Ni-Er alloy; (2) The Mg-Ni-Er alloy is prepared into Mg-Ni-Er alloy powder to obtain a magnesium-based hydrogen storage material.

6. The preparation method according to claim 5, characterized in that: The preparation method meets one or more combinations of the following conditions: (a) In step (1), the purity of the magnesium ingot is ≥99%; (b) In step (1), the smelting comprises: smelting in a vacuum smelting furnace in a first stage and a second stage, the power of the first stage is ≥15 kW, and the power of the second stage is ≥35 kW; the smelting time of the first stage and the second stage are both ≥5 min; (c) In step (2), preparing the Mg-Ni-Er alloy into Mg-Ni-Er alloy powder comprises: crushing the Mg-Ni-Er alloy, and ball milling to obtain the Mg-Ni-Er alloy powder; (d) The diameter of Mg-Ni-Er alloy powder is ≤15um.

7. The preparation method according to claim 6, characterized in that: Ball milling meets one or more of the following conditions: 1) Ball milling under inert gas environment; 2) Ball milling: mechanical wet ball milling.

8. The preparation method according to claim 7, characterized in that: Mechanical wet ball milling meets one or more of the following conditions: (i) the ball milling solvent is selected from one or more combinations of n-heptane, ethanol, isopropanol or ethyl acetate; (ii) The ball-to-material ratio is (20-40):1; (iii) the ball milling speed is 250 rpm-350 rpm; (iv) The diameters of the grinding balls are 8 mm and 6 mm.

9. A hydrogen storage device, characterized in that: The magnesium-based hydrogen storage material is prepared from the magnesium-based hydrogen storage material according to any one of claims 1 to 4.

10. Use of the magnesium-based hydrogen storage material according to any one of claims 1 to 4 in solid-state hydrogen storage.

Citation Information

Patent Citations

  • Preparation method of hydrogen storage nano material containing magnesium erbium nickel

    CN101550561A

  • Magnesium-based nano-composite hydrogen storage material with dispersively distributed catalytic phase and preparation method of material

    CN107345282A

  • Nickel-containing high-toughness controllable degradation magnesium alloy material as well as preparation method and application thereof

    CN109295368A

  • High-toughness rapidly-degradable Mg-Er-Ni alloy for underground fracturing and preparation method of high-toughness rapidly-degradable Mg-Er-Ni alloy

    CN114908280A

  • Frame type locally degradable titanium / magnesium composite material and preparation method thereof

    CN118345288A